Outcome of right ventricular assist device implantation following left ventricular assist device implantation: Systematic review and meta-analysis. (November 2022) - Reid, Gregory; Mork, Constantin; Gahl, Brigita; Appenzeller-Herzog, Christian; von Segesser, Ludwig K; Eckstein, Friedrich; Berdajs, Denis A
Objectives: The main aim was a systematic evaluation of the current evidence on outcomes for patients undergoing right ventricular assist device (RVAD) implantation following left ventricular assist device (LVAD) implantation. Methods: This systematic review was registered on PROSPERO (CRD42019130131). Reports evaluating in-hospital as well as follow-up outcome in LVAD and LVAD/RVAD implantation were identified through Ovid Medline, Web of Science and EMBASE. The primary endpoint was mortality at the hospital stay and at follow-up. Pooled incidence of defined endpoints was calculated by using random effects models. Results: A total of 35 retrospective studies that included 3260 patients were analyzed. 30 days mortality was in favour of isolated LVAD implantation 6.74% (1.98–11.5%) versus 31.9% (19.78–44.02%) p = 0.001 in LVAD with temporary need for RVAD. During the hospital stay the incidence of major bleeding was 18.7% (18.2–19.4%) versus 40.0% (36.3–48.8%) and stroke rate was 5.6% (5.4–5.8%) versus 20.9% (16.8–28.3%) and was in favour of isolated LVAD implantation. Mortality reported at short-term as well at long-term was 19.66% (CI 15.73–23.59%) and 33.90% (CI 8.84–59.96%) in LVAD respectively versus 45.35% (CI 35.31–55.4%) p ⩽ 0.001 and 48.23% (CI 16.01–80.45%) p = 0.686 in LVAD/RVAD group respectively. Conclusion: Implantation of a temporary RVAD is allied with a worse outcome during the primary hospitalization and at follow-up. Compared to isolated LVAD support, biventricular mechanical circulatory support leads to an elevated mortality and higher incidence of adverse events such as bleeding and stroke.